Testing the validity of ICD-11 PTSD and CPTSD among refugees in treatment using latent class analysis - Maria Louison Vang; Sabrina Brødsgaard Nielsen; Mikkel Auning-Hansen; Ask Elklit (Torture)
Introduction: The WHO has proposed posttraumatic stress (PTSD) and Complex PTSD (CPTSD) trauma-related ‘sibling’-disorders in ICD-11. The proposal has received support from research among clinical and community samples alike but only few studies have tested the validity of these disorders in a sample of refugees using the International Trauma Questionnaire especially designed for assessment of ICD-11 PTSD and CPTSD.